(untitled) (Singaporean Journal of Business Economics and Management, 2013)
There are several discussions about knowledge representation but not in its usage in solving the real problems. So we introduce the definition, application and the use of expert system in this article. Expert system resolves those real problems which generally require an expert human to solve. Expert system is a branch of artificial intelligence and is developing quickly. We shouldn’t forget although expert system is a beneficial system; it cannot solve all the problems. At the end of this article we mentioned to some of its problems.